Crowdfunding and financial system models - Waszkiewicz, Aneta Ewa (Crowdfunding a modele systemu finansowego, 2020)
The subject of the analysis is the relationship between the development of crowdfunding and the model and development of the financial system. The research goal is an attempt to answer the question: does the dynamic development of crowdfunding as a radical financial innovation result from the model of the financial system and its structure, or the level of its innovation and digitization, or do these factors not play a significant role. Literature analysis, statistical and descriptive analysis and ranking method were used as the research method. Based on the results, it should be stated that there is no clear division of financial systems into a market or bank-based model among Western European countries, while financial systems are increasingly divided into those innovative and traditional. The development of the financial market, combined with a high level of innovation and digitization of the economy, favours the development of financial innovation in the form of crowdfunding
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 2, s. 97-108
Keywords: crowdfunding; financial system; market-based financial system model; bank-based model; innovation; system finansowy; model rynkowy systemu finałowego; model bankowy systemu finałowego; innowacja